(untitled) (Research, Society and Development, 2020)
Depression and anxiety disorders may have physiological and behavioral effects that may be linked to heart disease or, more broadly, to metabolic conditions such as obesity, metabolic syndrome and dyslipidemias. The present study had as objective to evaluate the repercussion of lipid emulsion induced by a high fat lipid emulsion (EATG) using modified methodology on the behavioral parameters and memory of adult wistar rats. The animals were divided into two groups: Control Group - GC (n = 10) and dyslipidemic group - GCD (n = 8). The GCD group was treated with EATG, via gavage 1mL / 100 g of weight, for two weeks, after induction received standard commercial diet for another 4 weeks. The GC was submitted to the same gavage condition, distilled water being administered in the same proportion. We analyzed biochemical parameters, visceral fats, anxiety parameters using the open field test and the Labyrinth in High Cross and for short term memory evaluation; the object recognition test was performed using the open field apparatus. As for the effect of the protocol inducing dyslipidemia, it was observed that treatment with EATG with partial substitution of cholesterol by egg yolk was able to induce dyslipidemia. Regarding the results in the open field test, no parameter presented statistical difference and in the high cross maze test only the rearing parameter presented statistical difference. In the recognition of objects when comparing the groups, there was no statistical difference. Therefore, such results demonstrate that the new methodology was able to induce dyslipidemia but was not able to induce changes in the anxiety and memory behavior of the animals.